2014
DOI: 10.1016/j.jaci.2014.02.042
|View full text |Cite|
|
Sign up to set email alerts
|

Host natural killer immunity is a key indicator of permissiveness for donor cell engraftment in patients with severe combined immunodeficiency

Abstract: BackgroundSevere combined immunodeficiency (SCID) can be cured by using allogeneic hematopoietic stem cell transplantation, and the absence of host immunity often obviates the need for preconditioning. Depending on the underlying genetic defect and when blocks in differentiation occur during lymphocyte ontogeny, infants with SCID have absent or greatly reduced numbers of functional T cells. Natural killer (NK) cell populations are usually absent in the SCID-X1 and Janus kinase 3 forms of SCID and greatly reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 18 publications
1
30
0
1
Order By: Relevance
“…Therefore, it is possible that the T-precursor niche is occupied by the recipient cells, which might result in the competition during the process of donor T-cell maturation. Our results are in line with the report by Hassan et al, 14 which indicated that NK + SCID was less permissive for donor T-cell engraftment and the peripheral blood T-cell numbers were significantly lower in NK + SCID patients than in NK − SCID patients after HSCT without conditioning. They suggested that the thymus with recipient T-cell precursors might affect the process of T-cell reconstitution after HCST without conditioning.…”
supporting
confidence: 93%
“…Therefore, it is possible that the T-precursor niche is occupied by the recipient cells, which might result in the competition during the process of donor T-cell maturation. Our results are in line with the report by Hassan et al, 14 which indicated that NK + SCID was less permissive for donor T-cell engraftment and the peripheral blood T-cell numbers were significantly lower in NK + SCID patients than in NK − SCID patients after HSCT without conditioning. They suggested that the thymus with recipient T-cell precursors might affect the process of T-cell reconstitution after HCST without conditioning.…”
supporting
confidence: 93%
“…NK-type SCID individuals have enhanced survival with allogeneic stem cell transplantations compared with NK+ SCID patients 26 , while the presence or absence of B cells did not impact success in such patients. In addition, 33% of NK+ SCID stem cell recipients required additional procedures, including pretransplant myeloablation and/or radiation, while only 8% of NK-recipients required such procedures 26 .…”
Section: Severe Combined Immunodeficiency: Mutations and Cellular Promentioning
confidence: 87%
“…ТКИН характеризуются глубокой Т-клеточной лимфопенией или олигоклональными нефункцио-нальнымиТ-клетками(нарушениеТ-клеточнойдиф-ференцировки),какприОмен-синдроме.Отсутствие Т-клеточного иммунитета, а также В-и ЕК-клеток принекоторыхТКИНпредставляетсобойуникальное условиедляприживлениядонорскихклетокиопреде-ляет выбор режима кондиционирования (чаще ис-пользуютRICилитрансплантациюбезкондициони-рования) [2,14,22]. Во многих исследованиях, как ивнашем,показано,чтоупациентовсТКИНсубпо-пуляцияТ-лимфоцитовчащедонорскаядажеприот-сутствии кондиционирования [17,18,23,24], а для приживлениядонорскихмиелоидныхиВ-клетокпри В+ТКИНнеобходимопроведениеподготовительно-горежимапередаллоТГСК [18,[23][24][25][26].…”
Section: трансплантация гемопоэтических стволовых клетокunclassified